Meningeal inflammation increases cerebrospinal fluid artemether concentrations in Papua New Guinean children treated with intramuscular artemether - Manning, L.; Laman, M.; Page-Sharp, Madhu; Salman, S.; Hwaiwhanje, I.; Morep, N.; Siba, P.; Mueller, I.; Karunajeewa, H.; Davis, T. (American Society for Microbiology, 2011)
Although the artemisinin-associated neurotoxicity identified in vitro and in animal studies has not been confirmed clinically, only one adult study has measured cerebrospinal fluid (CSF) concentrations after administration of conventional doses. Potential artemisinin neurotoxicity could be serious in children, especially those with meningitis and, consequently, a compromised blood-brain barrier. We measured CSF/plasma artemether and dihydroartemisinin (DHA) concentrations in 32 Papua New Guinean children with a mean age of 39 months with suspected or proven severe falciparum malaria who underwent a single lumbar puncture after intramuscular artemether administration. CSF artemether concentrations were 0 to 43.5 ug/liter and CSF concentration/plasma concentration ratios were 0 to 38.1%. DHA was measurable in CSF in only two children. The seven children with meningeal inflammation (CSF white cell count > 20/mm3) had higher CSF artemether concentration/plasma artemether concentration ratios than those without (median, 6.7% [interquartile ratio, 2.5 to 27.8%]% versus 0.0% [interquartile ratio, 0.0 to 2.5%]; P = 0.002). Meningeal inflammation was associated with a 4.6-fold increase in the CSF artemether concentration/plasma artemether concentration ratio in a population pharmacokinetic model. These data suggest that pharmacovigilance should be heightened when intramuscular artemether is given to severely ill children with evidence of meningeal inflammation.